Dependence of the Preload on the Tightening Torque for Hydraulic Plugs - Jurij Hladnik; Franc Majdič; Anže Čelik; Boris Jerman (Applied Sciences)
In hydraulics, threaded plugs are used to close various manufacturing holes and other fluid channels. They are preloaded to ensure sufficient sealing force. Since the range of recommended thread and underhead friction coefficients for preloaded threaded connections in the literature is very wide, they are not suitable for accurate determination of the preload–torque relationships of plug–valve connections. In the study, two non-standard plugs with metric threads were equipped with strain gauges and repeatedly tightened three times in valve housings under lubricated and unlubricated conditions. The preload and tightening torque were measured. (1) Although the plug–valve connections had a similar geometry with the same surface roughness of the contacting surfaces, the average overall friction coefficient (uniform thread and underhead friction coefficient) and torque coefficient differed between the two connections in the unlubricated and lubricated conditions by 16% and 18%, respectively. This indicates that even small geometrical differences can have a considerable influence on these coefficients. The overall friction and torque coefficients were between 8% and 17% higher in the unlubricated condition than in the lubricated condition (not statistically proven). (2) The overall friction and torque coefficients decreased with repeated tightening under lubricated conditions. This influence decreased with the number of tightening repetitions. (3) Consideration of the minimum and maximum thread and underhead friction coefficients given in VDI 2230 would lead to an error in the estimated preload of −15% to +86%. In conclusion, for accurate determination of the preload–torque relationship of the plug–valve connections, measurements considering repeated tightening are crucial. These should be performed for each type and size of plug–valve connection separately. To minimize the repeated tightening influence, it is recommended to re-tighten the connections several times before leaving production.